A body map of super-enhancers and their function in pig - Yang, Youbing; Li, Xinyue; Meng, Zhu; Liu, Yongjian; Qian, Kaifeng; Chu, Mingxing; Pan, Zhangyuan (Frontiers in Veterinary Science, 2023)
Super-enhancers (SEs) are clusters of enhancers that act synergistically to drive the high-level expression of genes involved in cell identity and function. Although SEs have been extensively investigated in humans and mice, they have not been well characterized in pigs. Here, we identified 42,380 SEs in 14 pig tissues using chromatin immunoprecipitation sequencing, and observed that approximately 40% of normal enhancers (NEs) form SEs. Compared to NEs, we found that SEs were more likely to be enriched with an activated enhancer and show activated functions. Interestingly, SEs showed X chromosome depletion and short interspersed nuclear element enrichment, implying that SEs play an important role in sex traits and repeat evolution. Additionally, SE-associated genes exhibited higher expression levels and stronger conservation than NE-associated genes. However, genes with the largest SEs had higher expression levels than those with the smallest SEs, indicating that SE size may influence gene expression. Moreover, we observed a negative correlation between SE gene distance and gene expression, indicating that the proximity of SEs can affect gene activity. Furthermore, gene ontology enrichment and motif analysis revealed that SEs have strong tissuespecific activity. For example, the CORO2B gene with a brain-specific SE shows strong brainspecific expression, and the phenylalanine hydroxylase gene with liver-specific SEs shows strong liver-specific expression. In this study, we illustrated a body map of SEs and explored their functions in pigs, providing information on the composition and tissue-specific patterns of SEs. This study can serve as a valuable resource of gene regulatory and comparative analyses to the scientific community and provides a theoretical reference for genetic control mechanisms of important traits in pigs.